The Epidemiology and Prognosis of Cerebral Venous Sinus Thrombosis in a Third Level Hospital - José David Galián Ramírez; Vladimir Rosa Salazar; Leticia Guirado Torrecillas; Sonia Otálora Valderrama; María Encarnación Hernández Contreras; María del Mar García Méndez; Bartolomé García Pérez (Archives of Hematology Case Reports and Reviews - Peertechz Publications, 2017)
Objectives: To analyze several characteristics of patients with cerebral venous sinus thrombosis in a third level hospital and to find any factors that could be related to poor progress. Materials and methods: A retrospective study was carried out of patients hospitalized from 2000 to 2014 and diagnosed with cerebral venous sinus thrombosis. Results: 55 patients with an average age of 30.2 years old were included in the study. 73.1% had an associated risk factor. 72.7% received anticoagulation treatment during the acute phase, while 67.2% received long-term anticoagulation treatment for an average period of 5.3 months. 58.1% of patients developed complications deriving from the disease itself, 5.4% died, therefore no statistically significant association was found with any of the variables studied. Conclusions: Cerebral venous sinus thrombosis is a rare entity. This series, the patients were young, with a very high rate of complications (58%), although with low mortality (5%), which prevented us from finding factors associated with a bad prognosis..